(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Born from the conception of “sovereignty as responsibility”, the principle of “responsibility to protect” (R2P) started and developed, in a great measure, in the context of internal displacements. Its intellectual roots could be traced to the international strategies of protection and assistance to internally displaced persons (IDPs), during the 1990s. In the wake of an increasing tendency to disassociate R2Pfrom IDP, the article examines the initiative of the African Union (AU) which, through the Kampala Convention, redirects the debate and locates the internal displacements in the normative and operative realm of this principle (R2P), and at the same time contributes to its advancement.